The Europa international foundation directory 2007 (Routledge, 2007)
Provides an un-paralleled guide to the foundations, trusts, charitable and grant-making NGOs, and other similar not-for-profit organizations of the world. This title presents a comprehensive picture of third sector activity on a global scale. It includes comprehensive information on this sector.